Romiplostim in children with immune thrombocytopenia: a phase 3, randomised, double-blind, placebo-controlled study. Issue 10039 (2nd July 2016) - Tarantino, Michael D; Bussel, James B; Blanchette, Victor S; Despotovic, Jenny; Bennett, Carolyn; Raj, Ashok; Williams, Bronwyn; Beam, Donald; Morales, Jaime; Rose, Melissa J; Carpenter, Nancy; Nie, Kun; et al.
Summary: Background: The thrombopoietin receptor agonist romiplostim could be an effective treatment in symptomatic children with persistent or chronic immune thrombocytopenia. We aimed to assess whether romiplostim is safe and effective in children with immune thrombocytopenia of more than 6 months' duration. Methods: In this phase 3 double-blind study, eligible participants were children with immune thrombocytopenia aged 1 year to 17 years and mean platelet counts 30 × 10 9 /L or less (mean of two measurements during the screening period) with no single count greater than 35 × 10 9 /L, and were recruited from 27 sites in the USA, Canada, and Australia. Participants were randomly assigned (2:1) through the interactive voice response system to receive weekly romiplostim or placebo for 24 weeks stratified by age (1 year to <6 years, 6 years to <12 years, 12 years to <18 years), adjusting the dose weekly from 1 μg/kg to 10 μg/kg to target platelet counts of 50–200 × 10 9 /L. Patients and investigators were blinded to the treatment assignment. The primary analysis included all randomised patients and the safety analysis included all randomised patients who received at least one dose of investigational product. The primary endpoint, durable platelet response, was defined as achievement of weekly platelet responses (platelet counts ≥50 × 10 9 /L without rescue drug use in the preceding 4 weeks) in 6 or more of the final 8 weeks (weeks 18–25). This study is registered withClinicalTrials.gov, NCT 01444417 . Findings: Between Jan 24, 2012, and Sept 3, 2014, 62 patients were randomly assigned; 42 to romiplostim and 20 to placebo. Durable platelet response was seen in 22 (52%) patients in the romiplostim group and two (10%) in the placebo group (p=0·002, odds ratio 9·1 [95% CI 1·9–43·2]). Durable platelet response rates with romiplostim by age were 38% (3/8) for 1 year to younger than 6 years, 56% (10/18) for 6 years to younger than 12 years, and 56% (9/16) for 12 years to younger than 18 years. One (5%) of 19 patients in the placebo group had serious adverse events compared with 10 (24%) of 42 patients in the romiplostim group. Of these serious adverse events, headache and thrombocytosis, in one (2%) of 42 patients in the romiplostim group, were considered treatment related. No patients withdrew due to adverse events. Interpretation: In children with chronic immune thrombocytopenia, romiplostim induced a high rate of platelet response with no new safety signals. Ongoing romiplostim studies will provide further information as to long-term efficacy, safety, and remission in children with immune thrombocytopenia. Funding: Amgen Inc.